In search of Schrodinger's cat : quantum physics and reality - Gribbin, John, 1946- (Toronto : Bantam Books, 1984)
An astrophysicist offers an introduction to the theoretical principles, practical applications, and far-reaching implications of quantum physics and quantum mechanics.
pt. 1. The quantum. 1. Light : Waves of particles? ; Wave theory triumphant -- 2. Atoms : Nineteenth-century atoms ; Einstein's atoms ; Electrons ; Ions ; X rays ; Radioactivity ; Inside the atom -- 3. Light and atoms : The blackbody clue ; An unwelcome revolution ; What is h? ; Einstein, light, and quanta -- 4. Bohr's atom : Jumping electrons ; Hydrogen explained ; An element of change: God's dice ; Atoms in perspective ; Chemistry explained -- pt. 2. Quantum mechanics. 5. Photons and electrons : Particles of light ; Particle/wave duality ; Electron waves ; A break with the past ; Pauli and exclusion ; Where next? -- 6. Matrices and waves : Breakthrough in heligoland ; Quantum math ; Schringer's theory ; A backward step ; Quantum cookery -- 7. Cooking with quanta : Antimatter ; Inside the nucleus ; Lasers and masers ; The mighty micro ; Superconductors ; Life itself -- pt. 3. And beyond. 8. Chance and uncertainty : The meaning of uncertainty ; The Copenhagen interpretation ; The experiment with two holes ; Collapsing waves ; Complementarity rules -- 9. Paradoxes and possibilities : The clock in the box ; The'EPR paradox' ; Time travel ; Einstein's time ; Something for nothing ; Schringer's cat ; The participatory universe -- 10. The proof of the pudding : The spin paradox ; The polarization puzzle ; The Bell test ; The proof ; What does it mean? ; Confirmation and applications -- 11. Many worlds : Who observes the observers? ; Schringer's cats ; Beyond science fiction ; Beyond Einstein? ; A second look ; Beyond Everett ; Our special place -- Unfinished business : Twisted space-time ; Broken symmetry ; Supergravity ; Is the universe a vacuum fluctuation? ; Inflation and the universe.
Includes bibliographical references : (pages 277-289) and index.
Keywords: Schrodinger, Erwin, -- 1887-1961.; Quantum theory -- History; Reality